THE WALKABILITY OF TRANSIT ORIENTED DEVELOPMENT (TOD): A CASE STUDY OF BANGKOK METROPOLITAN, THAILAND - PAWINEE IAMTRAKUL; I-soon Raungratanaamporn; Jirawan Klaylee; Sararad Chayphong (Lowland Technology International, 2021)
To cope with the crisis of traffic congestion, Transit Oriented Development (TOD) which promotes moving people rather than cars becomes a powerful tool to be considered to alleviate urban mobility problem. To increase transit patronage, non-motorization travel, revenue increase, and urban diversity with livability enhancement, consideration on creative physical form of urban spaces in proximity to transit station must be evaluated. This study considered all aspects of transit station area within walking distance to attract physical activity and balance transportation by incorporating useful variables on evaluation of walking environment within the TOD. This study selected 10 mass transit (sky train) stations in Bangkok, Thailand to investigate the walkability of transit development, and recommend a suitable development of station area’s method that could provide greater accessibility in higher-density settings for non-auto commuting. This could be an explicit policy objective to provide an alternative approach incorporating transportation system with an efficient land use patterns through TOD, with the aim of using the strategic location in the walkability of mass transit stations as an integral part of the existing and future urban development.